Olfactory Sensitivity Is Related to Erectile Function in Adult Males - Deng, Hui-yi; Feng, Jia-rong; Zhou, Wen-hao; Kong, Wei-feng; Ma, Gong-chao; Hu, Teng-fei; Luo, Shao-ge; Xi, Yu; Zhang, Yan; Yang, Qin-tai (Frontiers in Cell and Developmental Biology, 2020)
Background The olfactory system influences human social behavior, in particular the selection of a spouse. However, there is currently a lack of clinical research on the relationship between the olfactory system and erectile dysfunction (ED) in adult males. Aim We explored the association between olfactory sensitivity and erectile function and its possible mechanisms. Results A total of 574 patients, adult males aged between 19 and 42 years, diagnosed with ED in the Department of Infertility and Sexual Medicine of the Third Affiliated Hospital of Sun Yat-sen University from 2015 to 2018 were analyzed retrospectively. Among them, 115 patients (20.03%) had rhinologic diseases (RDs). In addition, in 201 adult male patients who underwent nasal surgery in the ENT department from 2012 to 2016, including 29 (14.43%) with ED, nasal congestion, nasal discharge, and hyposmia were the most common complaints based on the numerical rating scale (NRS). Furthermore, a prospective study was performed in a total of 102 sequential outpatients (male adults) with RD only (n = 46), ED only (n = 42) and both RD and ED (n = 14) in 2019, together with 40 healthy (male adults) volunteers as controls. The results showed that ED patients with RD had severe nasal discomfort and decreased erectile function (P < 0.0001). The olfactory sensitivity of patients with ED was lower than that of the controls, and patients with both ED and RD had the worst olfactory sensitivity (P < 0.0001). Spearman correlation analyses showed that sense of smell was positively correlated with the International Index of Erectile Function-5 score (R = 0.507, P ≤ 0.0001) and the Erection Hardness Scale score (R = 0.341, P < 0.0001). Logistic regression analyses showed that having an olfactory disorder (OD), RD, age, and visual analog scale (VAS, over 5) score were risk factors for ED outcome, indicating that OD patients had a 16.479-fold increased risk for an ED outcome (P < 0.05). Conclusion A significant correlation was detected between olfactory sensitivity and erectile function in adult males. In particularly, impairment of olfactory sensitivity is more common in patients with both ED and RD than in patients suffering from a single disease.